Development of learning modules for floor gymnastics based on an independent curriculum for students - Afrido Romansyah; Wilda Welis; Zulbahri Zulbahri; Ahmad Chaeroni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aimed to develop and evaluate a Kurikulum Merdeka-based floor gymnastics module to enhance students’ psychomotor skills. The module was developed using the ADDIE model, validated by content and media experts, and implemented with 47 Grade X students over four sessions. Data were collected through pretests and posttests, observations, interviews, and questionnaires, and analyzed using paired t-tests, N-Gain, and thematic analysis. Results showed significant improvements in forward roll (53.6%), backward roll (68.4%), and candlestick (66.0%) skills, with p < 0.001. Student and teacher feedback highlighted clarity, engagement, and ease of use. The module proved valid, practical, and effective, and can be adapted to similar contexts, although further development is needed to improve accessibility, differentiation, and practice duration.